Improving vasculoprotective effects of MSCs in coronary microvessels – benefits of 3D culture, sub-populations and heparin - Bumroongthai, Kobkaew; Kavanagh, Dean P. J.; Genever, Paul; Kalia, Neena (Frontiers in Immunology, 2023)
PLEASE NOTE THAT DUE TO THE CHANGES THE REVIEWERS REQUESTED, THE ABSTRACT IS NOW SLIGHLTY LONGER THAN THE WORD LIMIT AND HENCE DOES NOT FIT HERE